Analise da prevalência de depressão em idosas praticantes de exercício físico - Frankiw, Thais Patricia (2014)
Introduction: Currently the elderly population has increased quickly and without the monitoring necessary to maintain their quality of life. Among the aspects that negatively influence the health of senile populations, are psychological disorders, especially depression, which is disabling and impairing activities of daily living. Objective: This study aims to analyze the association between the prevalence of depression and the type of exercise practiced by elderly who participate in programs for seniors. This work is relevant for Physical Educators and Psychologists, because it exposes the number of older participants in exercise programs suffering from depression, and also to correlate activity between some modalities which presents individuals with lower disease incidence. Methodology: The study participants are intentional, convenient and voluntary character composed of 57 elderly over 60 years practicing hydrogymnastics (n = 20), gymnastics (n = 20) or stretching (n = 17) offered by the city government of Curitiba. The GDS-30 was used to classify depression, measures of central tendency, variability and Chi square (x 2) test were applied. Results: The mean age of participants was 72.79 (SD = 6.3), generally was classified mild depression to 21.1% (n = 12) of participants, and normal for 78.9% (n = 45), between modes to higher frequency of mild depression was found in hydrogymnastics 45% (n = 9), followed by gymnastics 10% (n = 2) and finally stretching 5.9% (n = 1). Positive association was observed between modalities and mild depression with x 2 = 10.72, p = 0.005, with an aerobics with the largest portion. It is not possible to assert that there is a relationship of cause and effect is not clear whether the hydrogymnastics leaves depressed participants or are depressive seeking this activity, but it was observed that the group of aerobics is the hardest hit by this psychopathology.